Shifting the CARASIL Paradigm: Report of a Non-Asian Family and Literature Review. Issue 4 (April 2015) - Menezes Cordeiro, Inês; Nzwalo, Hipólito; Sá, Francisca; Ferreira, Rita Bastos; Alonso, Isabel; Afonso, Luís; Basílio, Carlos
Abstract : Background and Purpose—: Cerebral autosomal recessive arteriopathy with subcortical infarcts and leukoencephalopathy (CARASIL) is a rare form of nonhypertensive cerebral small-vessel disease caused by mutations in the HTRA1 gene. CARASIL is characterized by early adulthood onset of subcortical infarcts, cognitive impairment, alopecia, and spondylosis. Until recently, this disorder was almost exclusively reported in the Asian population. Methods—: Description of the clinical, imaging, and genetic study of 2 siblings with CARASIL, with a brief comparative review of published non-Asian cases of the disease. Results—: Both patients exhibited the typical phenotype: cerebral small-vessel disease, spondylosis, and abnormal hair lost. Mutation screening was performed for NOTCH3 and HTRA1 genes. No mutations were found in NOTCH3 . The study revealed the presence of a homozygous c.496C>T substitution in HTRA1 in both siblings. Conclusion—: This report highlights the need of considering this entity in the differential diagnosis of cerebral small-vessel disease in young patients, even in the non-Asian populations. Abstract : Supplemental Digital Content is available in the text.